Congenital thrombocytopenia associated with a heterozygous variant in the MEIS1 gene encoding a transcription factor essential for megakaryopoiesis. (19th May 2022) - Steinberg-Shemer, Orna; Orenstein, Naama; Krasnov, Tanya; Noy-Lotan, Sharon; Marcoux, Nathaly; Dgany, Orly; Yacobovich, Joanne; Gilad, Oded; Shabad, Evelyn; Basel-Salmon, Lina; Tamary, Hannah
Abstract: The transcription factor MEIS1 (myeloid ectotrophic insertion site 1) is crucial for the maintenance of hematopoietic stem cells and for megakaryopoiesis. Germline variants in MEIS1 are associated with restless-leg syndrome, but were not previously shown to cause cytopenias. This is the first report of a patient with congenital thrombocytopenia associated with a sequence variant in MEIS1, presenting with early onset severe thrombocytopenia and mild signs of bone marrow stress. Whole exome sequencing revealed a de novo monoallelic splice site variant in MEIS1, NM_002398.3:exon4:c.432 + 5 G > C, leading to a premature stop codon. We propose that heterozygous mutations in MEIS1 may cause congenital thrombocytopenia.